Operations research techniques for scheduling chile's second division soccer league - Duran, Guillermo Alfredo (2012)
In this paper, we use operations research (OR) techniques to schedule the Second Division of the Chilean professional soccer league. The solution must satisfy a series of conditions requested by league officials. Because the teams generally travel long distances by bus, geographical restrictions are particularly important. We specify the scheduling problem and solve it using an integer linear programming (ILP) model that defines when and where each match is played, subject to constraints. For the most difficult instances, we formulate a second ILP model that generates home-away patterns and assigns them to the teams; we then run the model, which determines the match schedule. Chilean league officials have successfully used the models to schedule all five Second Division tournaments between 2007 and 2010, replacing the random scheduling methodology that they used previously. Since 2007, the two formulations have been adapted to various formats with which the Second Division has experimented; these include a quadruple round robin and a two-phase tournament with zonal and national phases. The application we present is one of a number of such projects that the authors and their colleagues developed over the past few years, and it represents an expansion of the use of OR techniques for managing tasks in Chilean soccer.